Development .. Concept and Identity in the Neoliberalism Phase - Saad , Faisal (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
For one reason or another, we find a kind of reduction of development into growth. This reduction has been a very serious reason of the failure or failure of development experiences in the majority of underdeveloped countries. Development is a historical project that intends to change the current social reality as a beginning for a construction of a new, more developed and civic, actuality, While growth in no more than an economic situation which is local and inconstant, and which is able to be presented in counting statistical expressions. Thus, development is a structural matter that requires specific economic, politic and social changes. while growth is a technical change that doesn’t necessarily require such recent changes. Development has always been the essential treatment for the structural and technological underdevelopment in the age of neoliberalism. And It’s not of the kind of classical capitalist development or "socialist" development in its Soviet vulgar version that collapsed at the beginning of this century. The logical conclusion is that the development that would be able in this new phase of capitalist globalization- to face the underdevelopment of underdeveloped countries, on both technical and structural sides, is actually a development that has a popular and national identity. This makes of it a kind of development that is concerned in the realization of to kinds of tasks: some are capitalist, and others are popularist. A development that holds such an identity has to be ruled by some equations. Maybe the most important of these equations is the social justice and the delinking. We understand this latter as getting the control on the linking itself, by the means of logics and mechanisms of the neoliberalism.